Optimization of chromium(VI) biosorption using gooseberry seeds by response surface methodology - J. Aravind; P. Kanmani; G. Sudha; R. Balan (Global Journal of Environmental Science and Management, 2016)
The current investigation presents the role of gooseberry (Phyllanthus acidus) seeds as an effective biosorbent for remediating chromium (VI)), a toxic heavy metal pollutant commonly found in effluents from tanneries and relevant industries. Biosorption was affected by pH, temperature and initial metal concentration. Furthermore, there is a need to understand the holistic effect of all variables to ascertain the best possible conditions for adsorption, therefore, these factors were considered and a total of 17 trials were run according to the Box Behnken design. Quadratic model had maximum R2 value (0.9984) and larger F value (1109.92). From the Analysis Of Variance table and R2 value, quadratic model was predicted to be the significant model with the best fit to the generated experimental data. The optimal parameters obtained from the contour plot for the maximum removal of chromium(VI) were initial metal concentration of 60 mg/L, pH value of 2, and temperature of 27°C. Under these conditions, maximum removal of 92% was obtained. Thus this biosorbent substantially eliminates chromium(VI) under optimized conditions, enabling its use in larger scale.